PROBLEMS OF COMPLIANCE WITH LITERARY LANGUAGE NORMS IN STUDENTS' SPEECH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the problems of compliance with literary language norms in students' speech from linguistic and pedagogical perspectives. The literary language norm is interpreted as an important and stable element of the language system, and its role in shaping speech culture is highlighted. During the research process, lexical, phonetic, orthoepic, grammatical, orthographic, and punctuation errors occurring in students' speech are analyzed, and the causes of their emergence are identified. In particular, the influence of dialects and vernaculars, the growing role of mass media and internet speech, as well as methodological shortcomings in the educational process are indicated as main factors. The article scientifically highlights the effectiveness of the communicative approach, text-based work, corrective and analytical exercises, and creative tasks in improving compliance with literary language norms. Additionally, the exemplarity of teacher speech and the importance of shaping language culture in the school environment are substantiated. The research results demonstrate the necessity of a conscious and systematic approach to literary language norms in developing students' speech literacy and communicative competence.